2014
DOI: 10.5296/ajfa.v6i2.5246
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital Performance of Indonesian Banking Sector: A Modified VAIC (M-VAIC) Perspective

Abstract: The paper seeks to estimate and analize the Modified VAIC (M-VAIC) for measuring the value-based performance of the Indonesian banking sector for year of 2009-2012. M-VAIC is a comprehensive model to measure Intellectual Capital Performance (ICP) based on Value Added Intellectual Coefficient (VAIC™). The findings of this study indicate that the value of M-VAIC of Indonesian banking sector has a rather long range, which is between -21.41 until 5.20. Based on M-VAIC scores, performance of IC is classified into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0
30

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(167 citation statements)
references
References 17 publications
9
128
0
30
Order By: Relevance
“…Kalkan, Bozkurt, and Arman, (2014) found that there is a positive relationship between intellectual capital, innovation, and corporate strategy and corporate performance companies operating in Antalya, Turkey. Ulum, Ghozali, and Purwanto, (2014), who analyzes the M-VAIC to measure the performance of the banking sector in Indonesia also found that Value Added is a function of capital employed and Intellectual Capital thus affecting the performance of the banking system. Nkundabanyanga (2016) found a positive relationship between the interactions of the elements of intellectual capital to financial performance observed in microfinance companies in the State Uganda.…”
Section: The Proportion Of Chinese Ethnic In the Board Of Directors Amentioning
confidence: 99%
“…Kalkan, Bozkurt, and Arman, (2014) found that there is a positive relationship between intellectual capital, innovation, and corporate strategy and corporate performance companies operating in Antalya, Turkey. Ulum, Ghozali, and Purwanto, (2014), who analyzes the M-VAIC to measure the performance of the banking sector in Indonesia also found that Value Added is a function of capital employed and Intellectual Capital thus affecting the performance of the banking system. Nkundabanyanga (2016) found a positive relationship between the interactions of the elements of intellectual capital to financial performance observed in microfinance companies in the State Uganda.…”
Section: The Proportion Of Chinese Ethnic In the Board Of Directors Amentioning
confidence: 99%
“…Another study conducted by Darabi et al (2012), which found that intellectual capital has a positive and significant impact on earnings quality, the conclusion shows that intellectual capital has a positive role in financial practice and reporting. Ulum (2008), also conducts research on the banking sector in Indonesia. The results also state that intellectual capital is statistically influential to firm performance and firm value.…”
Section: Intellectual Capital and Corporate Valuementioning
confidence: 99%
“…These measurements are based on research by Vishnu and Gupta (2013), Jacub (2012), Ulum (2008) and Nuryaman (2015). The intellectual capital in this study was proxied by VAICTM measured by the sum of value added of asset capital (VACE), Human Capital (VAHU) and structural capital ( …”
Section: Intellectual Capitalmentioning
confidence: 99%
“…Hal ini dapat tercipta melalui pengetahuan karyawan yang diproses dengan modal struktural yang akhirnya menghasilkan hubungan yang baik dengan pihak luar (Widiyaningrum, 2004). Berikut ini merupakan definisi dan konstruk dari modal intelektual (Wang dalam Ulum dan Ghozali, 2014).…”
Section: Customer Capitalunclassified